Görünmeyen El Metaforu - (:unkn) unknown (My University, 2008)
İktisadın bilimselleşme süreci 18. yüzyılın toplum organizasyonunun tahayyülünde somutlaşır. Bu süreç politik merkezli toplumsal düzenlemenin alternatifi olarak beliren “kendiliğinden düzen” “görünmeyen el” metaforunda somutlaşır ve piyasa olgusu ile bütünleşir. Toplumsalın tasavvuruna, örgütlenmesine ilişkin bu iki temel tez ve çatışması günümüze kadar canlığını korur ve hatta bu dönemin temel gerilim odaklarından birini oluşturur. Smith’de, iktisatçıdan çok filozof kimliği ile görünmez ele ekonomik ve ötesinde felsefi, sosyolojik bir içerik kazandırır ve döneminin liberalizminin genel yapısını oluşturur. Yazıda bu bağlamda, “görünmez el” metaforu tartışılacak ve Smithyen kontekstte dinsellikle din dışılık arasındaki yeri irdelenecektir. Buradan kalkılarak Smith’in liberalizminin ancak metafizik bir tasavvur içinde ve analitik bir yaklaşımla kavranabileceği ileri sürülecektir. Görünmez elin misyonunu ne ölçüde gerçekleştirebildiği de tartışmaya açılacaktır.

Process of becoming academical of economics is materialized in the apprehension of community organization of the 18th Century. This process is materialized at the metaphor of "spontaneous order" "invisible hand" that is occurred as an alternative to the political centered communal arrangement and integrates with the market phenomenon. These two basic arguments related to the imagination, organization of the communal and their conflicts keep its activity up until now and even constitute one of the main tension focuses of that term. Also Smith brings in content that is economical and beyond that philosophic, sociological to invisible hand by his philosopher identity instead of his economist one and constitutes the general structure of liberalism of that term. At the writing in this context, "invisible hand" metaphor will be discussed and its place between spirituality and being out of religion in Smithian context will be considered. Moving from this, it will be offered that Smith's liberalism can only be understood in a metaphysics imagination and with an analytical approach. Also at which grade invisible hand can implement its mission will be opened to discussion, too.
Invisible Hand Metaphor
Keywords: İktisat; İşletme